2016
DOI: 10.3762/bjoc.12.112
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of highly functionalized 2,2'-bipyridines by cyclocondensation of β-ketoenamides – scope and limitations

Abstract: SummaryThe scope of a flexible route to unsymmetrically functionalized bipyridines is described. Starting from 1,3-diketones 1a–e, the corresponding β-ketoenamines 2a–e were converted into different β-ketoenamides 3a–g by N-acylation with 2-pyridinecarboxylic acid derivatives. These β-ketoenamides were treated with a mixture of TMSOTf and Hünig’s base to promote the cyclocondensation to 4-hydroxypyridine derivatives. Their immediate O-nonaflation employing nonafluorobutanesulfonyl fluoride provided the expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…7.0 and ca. 6.0, respectively]; (ii) relatively good solubility in aqueous media (e.g., 5.9 mg/mL in water); (iii) potential applications in the brain (e.g., intraperitoneally administered bpy was able to prevent and reduce intracerebral hemorrhage in vivo); (iv) ease of structural transformations . In addition, previous studies of bpy reported its ability to regulate metal-mediated reactions in biological systems [e.g., reducing the formation of hydrogen peroxide triggered by Fe­(II/III)], , supporting its applicability in biology.…”
Section: Resultsmentioning
confidence: 96%
“…7.0 and ca. 6.0, respectively]; (ii) relatively good solubility in aqueous media (e.g., 5.9 mg/mL in water); (iii) potential applications in the brain (e.g., intraperitoneally administered bpy was able to prevent and reduce intracerebral hemorrhage in vivo); (iv) ease of structural transformations . In addition, previous studies of bpy reported its ability to regulate metal-mediated reactions in biological systems [e.g., reducing the formation of hydrogen peroxide triggered by Fe­(II/III)], , supporting its applicability in biology.…”
Section: Resultsmentioning
confidence: 96%
“…DCPFC was synthesized by the literature 53 and 2-(Pyridin-2-yl)Pyridine was described 54 . Methane Carboxylic acid was purified by the standard procedure and the fraction distilling at 118 o C was collected 55 2,6-DicarboxyPyridinium Fluoro chromate (DCPFC) is easily prepared by the reaction of pyridine-2,6-dicarboxylic acid with chromium trioxide in HF 53…”
Section: Methodsmentioning
confidence: 99%
“…In particular, these compounds can be obtained from 2,2’‐bipyridines via nucleophilic substitution of hydrogen by the reaction of methyllithium with the following oxidative aromatization of the σ H ‐adduct or by using cross‐coupling reactions . Additionally, various types of heterocyclization reactions were carried out, e . g .…”
Section: Methodsmentioning
confidence: 99%